A Microdose Cocktail to Evaluate Drug Interactions in Patients with Renal Impairment. Issue 2 (26th October 2020) - Tatosian, Daniel A.; Yee, Ka Lai; Zhang, Zufei; Mostoller, Kate; Paul, Erina; Sutradhar, Santosh; Larson, Patrick; Chhibber, Aparna; Wen, Jianzhong; Wang, Ya‐Juan; Lassman, Michael; Latham, Andrew H.; et al.
Abstract : Renal impairment (RI) is known to influence the pharmacokinetics of nonrenally eliminated drugs, although the mechanism and clinical impact is poorly understood. We assessed the impact of RI and single dose oral rifampin (RIF) on the pharmacokinetics of CYP3A, OATP1B, P‐gp, and BCRP substrates using a microdose cocktail and OATP1B endogenous biomarkers. RI alone had no impact on midazolam (MDZ), maximum plasma concentration (Cmax ), and area under the curve (AUC), but a progressive increase in AUC with RI severity for dabigatran (DABI), and up to 2‐fold higher AUC for pitavastatin (PTV), rosuvastatin (RSV), and atorvastatin (ATV) for all degrees of RI was observed. RIF did not impact MDZ, had a progressively smaller DABI drug‐drug interaction (DDI) with increasing RI severity, a similar 3.1‐fold to 4.4‐fold increase in PTV and RSV AUC in healthy volunteers and patients with RI, and a diminishing DDI with RI severity from 6.1‐fold to 4.7‐fold for ATV. Endogenous biomarkers of OATP1B (bilirubin, coproporphyrin I/III, and sulfated bile salts) were generally not impacted by RI, and RIF effects on these biomarkers in RI were comparable or larger than those in healthy volunteers. The lack of a trend with RI severity of PTV and several OATP1B biomarkers, suggests that mechanisms beyond RI directly impacting OATP1B activity could also be considered. The DABI, RSV, and ATV data suggest an impact of RI on intestinal P‐gp, and potentially BCRP activity. Therefore, DDI data from healthy volunteers may represent a worst‐case scenario for clinically derisking P‐gp and BCRP substrates in the setting of RI.